Tinjauan Fikih Terhadap Nasihat kepada Penguasa - Rachmat Bin Badani Tempo; Akhmad Hanafi Dain Yunta; Saifullah Bin Anshor (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2019)
This study aimed at identifying and examining definition and scope of the term ulil amri, important things to consider in giving advice to ulil amri, the way to give them advice, and Islamic jurisprudential view on “Peaceful Action”. This study employed qualitative-descriptive method with content analysis techniques and library research. The results of the study shows that: (1) ulil amri to whom Allah obligate obedience are scholars of rabbaniyyun and leaders as well as those who are in charge of Muslims; (2) some important things in giving advice to ulil amri, those are listening and obeying them in good matter, praying for them goodness and salvation, avoiding ghibah and degradation of ulil amri, cooperating in goodness and piety, being patience upon badness and wrongdoing of the leaders, and giving advice to ulil amri; (3) advising them secretly is the best way, but the scholars also advocate to advise them openly if that method more beneficial to leaders and community; (4) “Peaceful Action” is a matter of ijtihadiyyah in which the scholars have different views on it. Therefore, denying munkar both sir (secretly) and ‘alan (openly) is part of maqasid syar’iyyah that need to be implemented based on rules and considerations of goodness and badness.